Percepção e produção de sentido no ciberespaço: influência de elementos infográficos em decisões de acesso na Web - Lima, Paulo Alves de (2010)
Considering the current dissemination stage of the world wide web and the historical social repercussion which such presence evokes, this Master Thesis intents to provide subsidies to webdesign activity, developing knowledges that contribute to the process of infographics elements manipulation in the web interfaces construction. The study corpus, Brazilian websites graphical interfaces, required for its analysis, quali-quantitative empirical research that enables, through aesthetic dissection, the identification of the existence of dominating visual patterns in Brazilian websites interfaces. The results of this stage reference the elaboration of representative models, which in the following step passed by a test process and validation with the users. The successful achievement of these objectives made it possible to solve one of the major problems related to the research object, the assembly of an interface model capable of tracing and computing path of user access, identifying separately how the infographics elements of the screen are related to each other, in the reception context, to the surfer decision for the click-through. This road bared the existence evidences of aesthetic phenomenal in the research context, fact theoretically addressed through style viewpoint, which resulted in proposing a new approach to the webdesign, capable of bringing closer the cyberculture theoretical views and the empirical results produced nowadays. The theoretical framework of the dissertation is based on three great quadrants. In the first one is located the comprehension, in the applied social science context, of the historical social movie set where the cyberculture and its typical technologically mediated communication processes are inserted. On this stage, the references are Zygmunt Bauman, Paul Virilio, Neil Postman, Asa Briggs and Peter Burke. In a second moment, the computer graphic interfaces genesis is treated with their semantic machines and graphical metaphors; here the text dialog extends to propositions of Steven Johnson, Oliver Sacks, Philippe Breton and Walter Benjamin. Finally, follows a reflection about the webdesign and its conceptualaesthetic issues under the historical view of style and here the references are Adrian Frutiger, Josef Albers, Allen Hurkburt, Donis Dondis, Charles Peirce, Eugênio Trivinho e Lucia Santaella